1994
DOI: 10.1007/bf01517168
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with a synthetic peptide of C-reactive protein and interleukin 2: augmented survival and eradication of pulmonary metastases

Abstract: A synthetic peptide (RS-83277) derived from the structure of human C-reactive protein (CRP) was previously shown to have antitumor activity in three different murine tumor models when administered in multilamellar vesicles (MLV). The therapeutic effects were comparable to those seen with MLV-encapsulated native CRP. The present study evaluated the therapeutic and immunomodulatory effects of administering CRP peptide RS-83277 MLV simultaneously with low-dose recombinant interleukin-2 (IL-2) to C57Bl/6 mice bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The molecular weight is 1.3 k Da, which is about 100th of that of native CRP. The synthetic CRP has been reported to have a biological activity which is similar to that of native CRP [3, 4]. We demonstrated that synthetic CRP generally suppressed the production of the proinflammatory cytokines, TNF, and IL-12, from human macrophages, whereas it did not affect the IFN-γ production from NK cells and T cells.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The molecular weight is 1.3 k Da, which is about 100th of that of native CRP. The synthetic CRP has been reported to have a biological activity which is similar to that of native CRP [3, 4]. We demonstrated that synthetic CRP generally suppressed the production of the proinflammatory cytokines, TNF, and IL-12, from human macrophages, whereas it did not affect the IFN-γ production from NK cells and T cells.…”
Section: Discussionmentioning
confidence: 52%
“…Several reports suggested that CRP as well as functional CRP peptides have positive and regulatory effect on the innate immunity against infections and tumors [3, 4], however, the role of CRP on innate immunity has not been fully elucidated. We have recently reported that pretreatment with synthetic CRP prevents mice from developing either lethal endotoxemia or E .…”
Section: Introductionmentioning
confidence: 99%
“…Deodhar et al ( 29 , 37 ) and Barna et al ( 54 ) reported anti-cancer CRP reagents were effective at preventing metastases and death. The studies by Kresl et al corroborate these findings but extend the understanding to emphasize that the conformation of CRP is a critical factor in eliciting the anti-metastatic effect.…”
Section: Early Studies Directly Comparing Pcrp and Mcrp In Animal Models Of Cancermentioning
confidence: 99%